Analysis of background variability of honey bee colony size. Issue 3 (31st March 2021) - ,; Ippolito, Alessio; Focks, Andreas; Rundlöf, Maj; Arce, Andres; Marchesi, Marco; Neri, Franco Maria; Rortais, Agnès; Szentes, Csaba; Auteri, Domenica
Abstract : In the context of the definition of specific protection goals for bees, risk managers asked EFSA to provide scientific background to support them in their decision‐making process about what needs to be protected and to what extent. The risk managers indicated that the derivation of a threshold of acceptable effects on colony size based on their variability was the preferred option for honey bees. This approach assumes that when evaluating a pesticide, the magnitude of acceptable effects should be set within the range of the background variability of colonies not exposed to pesticides. In this report EFSA used the BEEHAVE model to assess background variability of colony size in 19 EU environmental scenarios covering a range of geographical, climatic and beekeeping conditions. A comparison was made between the model outcome and the measurements performed on control groups of experimental field studies. The analysis of the background variability presented in this document should support risk managers in defining a threshold for colony size reduction that is considered acceptable.